Kontroversi Talak Tiga Sekaligus; Studi atas Hadis Talak Tiga Sekaligus Perspektif Ilmu Mukhtalif al-H?adîth - Moch. Nurcholis (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2015)
Discourse divorce three at once emerged from the hadîth T?awûs history, that Abû al-S?ahbâ. In the hadîth three divorces fell once considered one tune. However, it was found that a history states that ‘Abdullah ibn ‘Abbâs gave the law fell three divorces. This contradiction can be resolved through three approaches; al-jam’u wa al-tawfîq (compromise), naskh (substitution), tarjîh (Selection). From this, it is interesting to study discourse.